THE USE OF INTERACTIVE LEARNING TECHNOLOGIES IN THE PROCESS OF ECOLOGICAL TRAINING OF STUDENTS - O. Vasina; Y. Blinokhvatova; A. Blinokhvatov (Вестник Северо-Кавказского федерального университета, 2022)
The organization of the educational process in terms of competence-based approach provided by the Federal state standards of higher education requires the teacher to review the structure, forms of organization of activities, principles of interaction of subjects of the learning process. Interactive technologies that combine problem learning, information and communication technologies, and project methods are becoming promising learning technologies. The use of dialogical methods of communication, a variety of creative activities ofjoint search for the truth in the process of environmental training of students contributes to the formation of environmental-oriented component of competencies.